Unveiling Interconnectedness and Volatility Transmission: A Novel GARCH Analysis of Leading Global Cryptocurrencies - Kushwah, Silky Vigg; Hundal, Shab; Goel, Payal (International Journal of Economics and Financial Issues, 2024)
The cryptocurrency industry has grown erratically and at an alarming pace during its brief life. It has received massive attention from the practitioners, academicians, and especially media since Bitcoin was introduced in 2009. The current paper investigates the volatility dynamics of five major cryptocurrencies, namely Bitcoin, Ethereum, Litecoin, DASH and Ripple’s XRP. It discloses the impact of volatility in the prices of other cryptocurrencies on the Bitcoin’s price volatility. The time series of all the cryptocurrencies prices for the period 2016 to 2022 are considered and preliminary analysis highlights that there exists conditional volatility in all the cryptocurrencies which allows us to use the family of GARCH model. The research findings reveal the significant effect of asymmetric past shocks on the current volatility of Bitcoins. Further, the volatility of remaining virtual currencies are also significantly affecting the Bitcoin’s current volatility. Therefore, the present study unveils the absence of diversification benefits in the market of virtual assets as significant effect of price volatility of other digital coins has been found on the price volatility of Bitcoins. The practical implication of our study is that the findings offer new information for investors and portfolio managers, who are attracted to invest in or hedging strategies in cryptocurrencies.